Real effects of quantitative easing at the zero-lower bound: Structural VAR-based evidence from Japan - Heike Schenkelberg; Sebastian Watzka (Center for Economic Studies and ifo Institute (CESifo), 2011)
Using post-1995 Japanese data we propose a theory-based sign-restriction SVAR approach to identify monetary policy shocks when the economy is at the zero-lower bound. The identifying restrictions accord with predictions of corresponding DSGE models. Our results show that while a quantitative easing shock leads to a significant but temporary rise in output, the effect on inflation is not significantly different from zero. This suggests that while the Japanese Quantitative Easing experiment was successful in stimulating real activity in the shortrun, it did not lead to any increase in inflation. These results are interesting not only for Japan, but also for other advanced economies where monetary policy is currently constrained by the ZLB.
Keywords: E43; E51; E52; E58; 330; Geldpolitik; Wirkungsanalyse; Konjunktur; VAR-Modell; Schätzung; Japan